LB 2.59 Improving std screening in hiv care through implementation of self-collected extragenital swabs. (8th July 2017) - Park, Ina; Schapiro, Jeffrey; Hurley, Leo; Hare, C Brad; Slome, Sally; Flamm, Jason; Nelson, Lauren; Allerton, Michael
Abstract : Introduction: Screening for syphilis, gonorrhoea (GC) and chlamydia (CT) is recommended at least annually for HIV-positive men who have sex with men (MSM) in the United States (US). Recent analyses from the US Medical Monitoring Project demonstrate that STD screening of HIV-positive MSM remains far below that recommended by guidelines; specific data on extragenital GC/CT screening is not reported. We implemented a quality improvement intervention to improve STD screening (syphilis, GC/CT) in a large managed care organisation (16 centres) including didactic training and implementation of self-collected swabs for GC/CT. Methods: We analysed data from the Kaiser Permanente Northern California HIV Registry to calculate the proportion of MSM tested for syphilis and GC/CT (any site, rectal/pharyngeal site) at least once in the prior year. Laboratory validation of self-collected swabs was completed by 1/2014, rolled out at five centres by 12/2014, and 11 centres by 11/2016. Screening data were finalised for analysis in 1/2017. Three time periods were examined: baseline (6/2012), 1 year (11/2015), and 2 years (11/2016) post initial implementation of self-collection. Cochran-Armitage was used to test for trends. Results: During the study period, the denominator of eligible HIV-positive MSM increased from n=4499 to 5866. Annual screening for GC/CT (any site) significantly increased from 45.2% to 58.3% (ptrend <0.0001); extragenital GC/CT (among those screened) increased from 48.4% to 58.1% (ptrend <0.0001). Medical centres that implemented self-collected swabs within the first year reported higher extragenital screening rates than those who did not (60.6% vs 20.2%, p<0.0001), this difference persisted into year 2. Syphilis screening also increased from 73.6% to 76.8% (ptrend =0.0002). Conclusion: Implementation of self-collected GC/CT swabs is an effective intervention to increase STD screening among MSM in a large US managed care organisation. This intervention should be disseminated to other settings to improve currently suboptimal STD screening rates among MSM.